Efeitos do treinamento físico sobre a função cardíaca de ratas ovariectomizadas após o infarto do miocárdio - Simões, Simone Alves de Almeida (2014)
Approximately 40% of patients with myocardial infarction develop ventricular dysfunction with or without signs of heart failure, which adversely affect the quality of life, rates of hospitalization and mortality. The adverse ventricular remodeling after an acute ischemic event is the main factor involved in ventricular dysfunction and presents important differences between males and females. Studies have shown that the reduction of ovarian hormones can interfere negatively in important pathways related to the remodeling process. In addition, the regular practice of exercise training have shown important beneficial effects after myocardial infarction. Therefore, the aims of this study were to analyze the effects of exercise training in treadmill on the cardiac function, histologic and morphometric parameters and to check the protein expression of cardiac renin-angiotensin, oxidant and antioxidant systems in ovariectomized rats after myocardial infarction. Female Wistar rats (Rattus Norvegicus Albinus), with eight weeks of age were randomly divided into five groups at the time of ovariectomy: Control, OVX+SHAMSED, OVX+SHAMEF, OVX+IMSED and OVX+IMEF. Two weeks after the induction of myocardial infarction animals started the exercise training. The training protocol was carried out for a period of eight weeks, with duration of 60 min/day, five times a week with an interval of two days to rest. Fortyeight hours after the last day of exercise training protocol, animals were anesthetized for the achievement of the following analyzes. For the evaluation of cardiac function, the left ventricle was catheterized. Proteins expression in the left ventricle were performed by Western Blotting. Collagen and hypertrophy were assessed by histology and the citrate synthase activity by fluorimetry. After eight weeks of exercise training and myocardial infarction, animals of OVX+IMEF group showed a reduction in the expression of AT1 receptor and gp91phox, accompanied by an increase in catalase expression when compared to MI group (p<0.05). In addition, the exercise training prevented the increase in left ventricular end-diastolic pressure together with the reduction of dP/dt+. The cross-sectional area of the myocyte and collagen deposition were significantly increased in the MI group (p<0.05), but these changes were also prevented by exercise training. Together, these results demonstrates the beneficial effects promoted by the exercise training in treadmill on the cardiac remodeling process, impacting directly on the improvement of cardiac function in ovariectomized rats submitted to myocardial infarction